Predictors of extubation readiness in preterm infants: a systematic review and meta-analysis. Issue 1 (13th January 2019) - Shalish, Wissam; Latremouille, Samantha; Papenburg, Jesse; Sant'Anna, Guilherme Mendes
Abstract : Context: A variety of extubation readiness tests have already been incorporated into clinical practice in preterm infants. Objective: To identify predictor tests of successful extubation and determine their accuracy compared with clinical judgement alone. Methods: MEDLINE, Embase, PubMed, Cochrane Library and Web of Science were searched between 1984 and June 2016. Studies evaluating predictors of extubation success during a period free of mechanical inflations in infants less than 37 weeks' gestation were included. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. After identifying and describing all predictor tests, pooled sensitivity and specificity estimates for the different test categories were generated using a bivariate random-effects model. Results: Thirty-five studies were included, showing wide heterogeneities in population characteristics, methodologies and definitions of extubation success. Assessments ranged from a few seconds to 24 hours, provided 0–6 cmH2 O positive end-expiratory pressure and measured several clinical and/or physiological parameters. Thirty-one predictor tests were identified, showing good sensitivities but low and variable specificities. Given the high variation in test definitions across studies, pooling could only be performed on a subset. The commonly performed spontaneous breathing trials had pooled sensitivity of 95% (95% CI 87% to 99%) and specificity of 62% (95% CI 38% to 82%), while composite tests offered the best performance characteristics. Conclusions: There is a lack of strong evidence to support the use of extubation readiness tests in preterm infants. Although spontaneous breathing trials are attractive assessment tools, higher quality studies are needed for determining the optimal strategies for improving their accuracy.